Đặc điểm hoạt động của các đứt gãy ở khu vực hồ Phú Ninh - Thái Xuân trong Đệ Tứ hiện đại - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2018)
Characteristics of activity of the faults in the lake Phu Ninh - Thai Xuan area during Quaternary-present time